Delineation of microhemorrhage in acute hepatic encephalopathy using susceptibility-weighted imaging. Issue 3 (March 2016) - Benson, John C.; Payabvash, Seyedmehdi; Thalken, Gregory L.; Alonso, Juli; Rykken, Jeffrey; Ott, Frederick; McKinney, Alexander M.
Abstract: Introduction: Microhemorrhages (MH's) in patients with acute hepatic encephalopathy (AHE) have scarcely been described. This study set out to assess if MH's occur in characteristic locations and frequency in patients with AHE superimposed on chronic liver failure, and to determine if such findings correlate with the clinical and MRI severity. Materials and methods: Over a 4.5-year period, AHE patients with SWI MRI were included. The maximum plasma ammonia level (PAL), number and location of "frank" hemorrhages (>5 mm size) or MH's (<5 mm) on SWI, and severity of DWI and FLAIR were recorded. Susceptibility foci in the basal ganglia were disregarded, as those changes might represent common mineralization. The presence of MH's was correlated with the MRI and clinical severity. Results: Punctate MH foci were found in 18/38 (47.4%) patients. The most common locations were periventricular white matter (6/38 patients, 15.8%) and cerebral cortex (5/38, 13.2%). Of 47 MH's, only a tiny minority (8.5%) occurred in regions of abnormality on FLAIR or DWI. Both the MRI severity on FLAIR ( r  =  0.420, p  = 0.013 ) and DWI ( r   =  0.320, p   =   0.045 ) mildly correlated with clinical outcome, but the correlation was not significant after Bonferroni correction. No significant correlation was found between the number of MH's and the clinical score, clinical outcome, FLAIR severity, or DWI severity (range r   =   -0.083-0.152, p   =   0.363–0.618 ). The number of MH's was not significantly different among various vasculopathies. Foci on SWI improved in two patients following liver transplantation. Conclusion: SWI-positive foci outside of the basal ganglia (presumed MH's) are present in nearly half of AHE patients, but do not portend outcome. Regions with the most observed MH's were the periventricular white matter, cortical gray matter, and subcortical white matter.